Perancangan Website Menggunakan Platform SITE123 Sebagai Media Promosi Digital Bagi Umkm Munchies Bread Di Kota Bukittinggi - Leni Afriliani; Monica Sari; Zulfitri Yani; Sularno Sularno (CV. ITTC INDONESIA, 2026)
The development of information technology requires Micro, Small, and Medium Enterprises (MSMEs) to transform conventional marketing into digital strategies. Munchies Bread is an MSME in Bukittinggi specializing in bakery and hampers that previously relied solely on social media marketing, resulting in unintegrated and scattered information. This Project-Based Learning (PBL) activity aims to design and implement an informative and professional website for Munchies Bread using the SITE123 platform. The method encompasses multi-stage approaches, including MSME initial assessment, structured interviews, information architecture mapping, digital content design, deployment, and testing. The resulting website integrates primary menus: Home, About, Our Menu, Services, Testimonials, and Contact. The implementation shows that the web design successfully optimizes digital information management, strengthens professional brand credibility, and enhances accessibility for wider target markets. Future developments include integrating direct transactional e-commerce features and automated messaging services.